Maternal occupational exposures during early stages of pregnancy and adverse birth outcomes in the NINFEA birth-cohort - Antonio d’Errico; Maja Popovic; Costanza Pizzi; Giovenale Moirano; Chiara Moccia; Lorenzo Richiardi; Milena Maule (PLoS ONE, 2025)
Objectives Maternal occupational exposures during early pregnancy can be detrimental to foetus health and have short- and long-term health effects on the child. This study examined their association with adverse birth outcomes. Methods The study included 3938 nulliparous women from the Italian NINFEA mother-child cohort. Their occupational exposures during the first trimester of pregnancy were assessed through prospectively collected questionnaire information and job-exposure matrices. Associations between maternal exposures and birthweight, preterm birth, and delivery by caesarean section were analysed by multivariable linear and logistic regression models. An exploratory factor analysis was carried out to explore co-exposure profiles in association with birth outcomes. Results Women exposed to passive smoking at work and those who reduced their working hours during pregnancy were found to have an increased likelihood of all analysed birth outcomes. Children of mothers performing a demanding work were less likely to be born preterm [OR 0.72 (95% CI 0.54 to 0.95)] and more likely to have a higher birthweight [β = 40.4 g (95% CI 7.5 to 73.4)]. Maternal exposures to heat and dust were associated with a lower birthweight [β = -160.1 g (95% CI -299.6 to -20.7)] and increased odds of caesarean section [OR 6.99 (95% CI 2.36 to 25.47)], respectively. Conclusions This study provides some evidence of the selection of healthy population into the workforce and of association between work-related passive smoking, heat and dust and adverse birth outcomes.